Presencia Yugoslava en Chile - Rajevic, Andres (Revista Chilena de Humanidades, 2015)
This article offers a wide view of the Yugoslavian access to Chile, while tracing its causes and establishing the patterns which permit us to appreciate the significant contribution of their descendants to the progress of our country. The author maintains that the Yugoslav element has effectively assimilated the idiosyncracy and institutionality of the country of adoption without cutting links with the cultural heritage they brought from Europe.